The Globular State of the Single-Stranded RNA: Effect of the Secondary Structure Rearrangements. (9th August 2015) - Grigoryan, Zareh A.; Karapetian, Armen T.
Abstract : The mutual influence of the slow rearrangements of secondary structure and fast collapse of the long single-stranded RNA (ssRNA) in approximation of coarse-grained model is studied with analytic calculations. It is assumed that the characteristic time of the secondary structure rearrangement is much longer than that for the formation of the tertiary structure. A nonequilibrium phase transition of the 2nd order has been observed.